National Accounts Statistics: Analysis of Main Aggregates 2019 - United Nations Department of Economic; Social Affairs (United Nations, 2021)
This publication comprises analytical tables of national accounting aggregates for more than 200 countries and areas, for 1970-2019. It contains estimation methods for compiling data. Tables include analysis of data on GDP by structural components, classified into: 1) analysis of level and real growth of total and per capita GDP; 2) analysis of percentage shares of GDP by type of expenditure and gross value by economic activity; 3) analysis of economic development expressed in terms of real growth of GDP and its components by type of value, and 4) analysis of price development reflected by implicit price deflators of GDP.